Espécies nativas adequadas à arborização de uma cidade no ecótono Cerrado-Pantanal: seleção baseada em atributos morfológicos e serviços ecossistêmicos - REBEKA JAKELINY MACIEL RABELLO (2023)
Urban forestry provides several benefits, such as stabilization and improvement of microclimate, reduction of atmospheric and noise pollution, aesthetic improvement, and acts on physical and mental health in an urban environment. Proper planning and management of the urban environment are necessary to maintain the equilibrium of this ecosystem. At selecting species, it is necessary to consider their adaptation to the local climate, the area available for plant development, fruit size, leaf loss, root morphology and possible interference in buildings and infrastructure. So that these species can optimize their functions and contribute to the conservation and maintenance of genetic variability, it is essential to prioritize the planting of species native to the region. This study aims to present an open list of species indicated for planting in the urban afforestation of Aquidauana (MS), considering their morphological characteristics and ecosystem services provided according to the needs of the urban environment. This list was prepared based on a review of articles and dissertations on urban forestry in Aquidauana (MS), consulting the national herbaria system, plus the list of native species obtained from the i-Tree Species application. The following attributes were analyzed: height, diameter, wood density, leaf texture, leaf persistence, crown architecture and whether the species and roots are suitable for sidewalks and or open spaces. Our list contains 152 native plant species for street tree planting or public open spaces. We excluded species with allergenic potential, thorns, big or heavy fruits, and potential invaders. The list includes species with different attributes, allowing use in different situations and offering diverse ecosystem services. Some species are already being used in urban forests and can have their adaptability studied, and others can be incorporated into experimental plantings to study their behavior in an urban environment.